Kampanye Stop Bullying Dalam Perspektif Pendidikan Agama Kristen untuk Membangun Karakter Kasih di Kalangan Remaja SMK Media Informatika Dasana Indah - Ottovianus Otto; Joy Pratama; Licin Cermei Hulu; Delila Bili; Simon Simon; Tonji K. Feninlambir; Wanti R. Tamonob; Elsa Yusak; Ica Febria; Alfrianti Parantean (Vieka Wahana Semesta, 2025)
Abstract Bullying is one of the common problems occurring in school environments and has become a serious concern, especially among vocational high school (SMK) students. The forms of bullying are diverse, ranging from physical, verbal, and social to digital abuse (cyberbullying). Its impact on victims is significant, affecting both their mental well-being and academic performance. In this context, Christian Religious Education plays a vital role in shaping students' character so they can develop attitudes of love and empathy toward others. This Community Service activity aims to provide students of SMK Media Informatika Dasana Indah with an understanding of the dangers of bullying and the importance of applying love in daily life as a tangible expression of Christ’s teachings. The activity was conducted onsite using various methods such as lectures, interactive discussions, Q & A sessions, pre-tests and post-tests, as well as a declaration campaign themed “Stop Bullying, Let’s Be Part of the Movement of Love.” The materials covered included the definition, types, and psychological impact of bullying, and how Christian Religious Education contributes to instilling love based on John 13:34-35. The results of the activity showed improved student understanding and increased awareness of the need to create a safe, loving school environment that reflects Christian values. Abstrak Bullying adalah salah satu masalah yang sering terjadi di lingkungan sekolah dan menjadi perhatian serius, khususnya di kalangan siswa SMK. Bentuk-bentuk bullying sangat beragam, mulai dari fisik, verbal, sosial, hingga yang dilakukan melalui media digital (cyberbullying). Dampaknya sangat besar terhadap korban, baik dari segi mental maupun prestasi akademik. Dalam hal ini, Pendidikan Agama Kristen memiliki peranan penting dalam membentuk kepribadian siswa agar mampu mengembangkan sikap kasih dan empati terhadap sesama. Kegiatan Pengabdian kepada Masyarakat ini bertujuan untuk memberikan pemahaman kepada siswa SMK Media Informatika Dasana Indah mengenai bahaya bullying dan pentingnya penerapan kasih dalam kehidupan sehari-hari sebagai bentuk nyata dari ajaran Kristus. Kegiatan dilaksanakan secara langsung melalui berbagai metode seperti ceramah, diskusi interaktif, tanya jawab, pre-test dan post-test, serta deklarasi kampanye bertema “Stop Bullying, Ayo Jadi Bagian dari Gerakan Kasih”. Materi yang dibahas meliputi pengertian, jenis, serta dampak bullying, dan bagaimana pendidikan agama Kristen berkontribusi dalam menanamkan kasih berdasarkan Yohanes 13:34-35. Hasil kegiatan menunjukkan peningkatan pemahaman siswa, serta tumbuhnya kesadaran untuk menciptakan lingkungan sekolah yang aman, penuh kasih, dan mencerminkan nilai-nilai kristiani.